Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How could we show that: $$\prod_{0 \le j \ne i \le n} \frac{n+1-j}{i-j} = \frac{(n+1)!}{(n+1-i)\cdot i! \cdot (n-i)!}(-1)^{(n-i)} .$$

The module suggest we could reduce it by simply writing $$\prod_{0 \le j \ne i \le n} \frac{n+1-j}{i-j} = \frac{(n + 1)n \cdots (n + 1 − (i − 1))(n + 1 − (i + 1)) \cdots 1}{i(i − 1) \cdots 1 · (−1) \cdots (−(n − i))} ,$$ but I am not able to figure out the result from here.

Please explain your answer.

share|cite|improve this question
Why the formulas are so large? – Fabian May 30 '11 at 19:27
$\quad$Reduced. – Quixotic May 30 '11 at 19:30
Your fomula doesn't make sense unless $i$ is a fixed number. Where does it come from? – N. S. May 30 '11 at 19:31
$i$ is fixed it's a part of the problem that involves operation with la-granges interpolation formula. – Quixotic May 30 '11 at 19:38
That formula seems to evaluate to $$\frac{(n+1)!}{(n+1-i)\cdot i! \cdot (n-i)!}(-1)^{(n-i)}$$. Are you sure the n+1-i term is a factorial? – EuYu May 30 '11 at 19:52
up vote 4 down vote accepted

The numerator is

$$\prod_{0 \le j \ne i \le n} (n+1-j) \,.$$

By writing it term by term you get

$$(n+1)n(n-1)....(n+1-(i-1))(n+1-(i+1))...1 = \frac{(n+1)!}{n+1-i} \,.$$

The denominator is

$$\prod_{0 \le j \ne i \le n} (i-j)= [i(i-1)(i-2)...(i-(i-1))][(i-(i+1))(i-(i+1))...(i-n)] \,.$$

The first bracket is exactly $i!$, while the second is $(-1)(-2)...(-(n-i))$. By taking a minus out of each bracket you get $(-1)^{n-i}(n-i)!$.

Thus the denominator is $(-1)^{n-i}(n-i)!i!$.

Combining those you get exactly the formula Yuqing posted.

share|cite|improve this answer
This might be silly but when $(-1)^{n-i}$ goes in the numerator won't it would be $(-1)^{-n+i}$? what I am missing? – Quixotic May 30 '11 at 20:09
$\frac{1}{(-1)^{n-i}}=\frac{[(-1)^{n-i}]^2 }{(-1)^{n-i}}$ ;) – N. S. May 30 '11 at 20:12
Lol...clever ;) – Quixotic May 30 '11 at 20:13

\begin{equation} \prod_{0 \le j \ne i \le n} \frac{n+1-j}{i-j} = \frac{\prod_{0 \le j \ne i \le n}(n+1-j)}{\prod_{0 \le j \ne i \le n}(i-j)} \end{equation}

we can rewrite this as follows

\begin{equation} \frac{\prod_{0 \le j \ne i \le n}(n+1-j)}{\prod_{0 \le j \ne i \le n}(i-j)} = \frac{\prod_{0 \le j \le n}(n+1-j)}{(n+1-i) \times \prod_{0 \le j < i}(i-j) \times \prod_{i+1 \le j \le n}-(j-i)} \end{equation}

You can simplify the above expression to get an expression similar to what you have written. However, there is only $(n+1-i)$ instead of of the $(n+1-i)!$ in the denominator on the right hand side.

share|cite|improve this answer
what I am more interested to know, how are you rewriting? :)Precisely the denominator. – Quixotic May 30 '11 at 20:00
@debanjan, I'm simply splitting the product into two terms, one where $j<i$, where the individual terms of the product $\prod_{0\le j <i}(i-j)$ are all positive and another where the product is of negative terms. Try it with a small example (say $n=3$ and $i=1$) and it should be clear. – svenkatr May 30 '11 at 20:04

I assume only $j$ is the running index. Typically the way you have written the product on the left side it means that $i$ and $j$ are both running indices. You could mention this explicitly by using the following notation. $$\prod_{\substack{j=0\\ j \neq i}}^{n} \frac{n+1-j}{i-j}$$ Split the product into two $$\prod_{\substack{j=0\\ j \neq i}}^{n} \frac{n+1-j}{i-j} = \prod_{j=0}^{i-1} \frac{n+1-j}{i-j} \times \prod_{j=i+1}^{n} \frac{n+1-j}{i-j}$$ $$\prod_{j=0}^{i-1} \frac{n+1-j}{i-j} = \frac{(n+1)n(n-1)(n-2) \cdots (n-i+2)}{(i)!} = \frac{(n+1)!}{i! (n-i+1)!}$$ $$\prod_{j=i+1}^{n} \frac{n+1-j}{i-j} = (-1)^{n-i} \frac{(n-i)!}{(n-i)!} = (-1)^{n-i}$$ Hence, we get $$(-1)^{n-i} \frac{(n+1)!}{i! (n-i+1)!}$$

share|cite|improve this answer
Actually both i and j are running index in the actual problem,but you are right this is the better way to explain for this subproblem. – Quixotic May 30 '11 at 20:19

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.